Совершенствование системы качества малых гостиничных предприятий на примере малого гостиничного предприятия «Союз» города Москвы - Mukhortikova E. E. (Scientific studies: theory, methodology and practice, 2017)
In the process of the research, a comparative analysis of the services provided by the Soyuz hotel company was made to meet the basic standards of hotel services. As a result, a number of problems were identified, both technical and functional quality, and social quality of services. In connection with these, methodological and practical recommendations were proposed to improve the quality system of the services provided.
Keywords: система качества услуг; малое гостиничное предприятие; уровень персонала; удовлетворенность клиентов; quality of service system; small hotel company; staff level; customer satisfaction